KEDUDUKAN DAN APLIKASI PENDIDIKAN SAINS DI SEKOLAH DASAR - Desstya, Anatri (Universitas Muhammadiyah Surakarta, 2014)
Natural Science is basic science, which in its development wider and its application ofscience was born, namely technology. Science and technology are achieved by a nationis a benchmark for the progress of a nation. Through the process of education in elementaryschool, science has begun to be given. However, in the implementation, itraises some problems occurred and the nature of science is not in line if applicable,including: not or do not give the maximum opportunity for students to develop creativity,teaching material still feels off with the main problems that arise in the community,the process has not appeared skills in learning at school, and still conventional sciencelessons. Efforts to science education in elementary schools is indispensable to the era oftechnology in the future with respect to some aspects, namely: understanding the natureof science, know and understand the child’s developmental level, especially elementaryschool age children, relying on the theory of constructivism and developmental theoryof Jean Piaget, and apply scientific study combined with the various models of learningscience, among other constructivists, the inquiry, science process skills, STM (sciencetechnology society), integrated, interactive, learning cycle and CLIS (Children Learningin Science).